Interpreting Texts as Scripts:: The Lyric Model - Glauert, Amanda (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2013)
Faced with Steiner’s admission that writing cannot capture the actual experience of music in time, this article considers Goethe’s way of transforming texts into scripts for musical performance, using his lyric poem ‘An Lina’. Through this poem Goethe offers both theoretical and practical lessons in how to use texts to prepare and frame the transitory moment of performance; he outlines a four-staged model in which a written text becomes script, ready for being reassembled as text. The paper explores the wider ramifications of such a cyclical model of text making and text dismembering in relation to Beethoven’s setting of Herrmann’s ‘Der Bardengeist’. In this song Beethoven’s manipulation of contrasting time-frames invites an analytical interpretation of the act of performance. Beethoven’s perfecting of a musical text for ‘Der Bardengeist’ is compared with the more fluid referencing of an improvisatory performance practice in Reichardt’s setting of ‘An Lina’. However, there are aspects of Beethoven’s text which suggests it can also be taken as a script, as a scaffolding for preparing the experience of a performance moment rather than as a building in itself. In the lyric model, texts – and the musicological interpretations concerned with them – retain significance but in a changing context. They are not so much significant in themselves as in raising expectations for the far greater subtlety of the performance acts which they help prepare or frame.